2013
DOI: 10.1016/j.bpj.2013.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Design for Nonconsensus Protein-DNA Binding Affinity in the Vicinity of Functional Binding Sites

Abstract: Recent experiments provide an unprecedented view of protein-DNA binding in yeast and human genomes at single-nucleotide resolution. These measurements, performed over large cell populations, show quite generally that sequence-specific transcription regulators with well-defined protein-DNA consensus motifs bind only a fraction among all consensus motifs present in the genome. Alternatively, proteins in vivo often bind DNA regions lacking known consensus sequences. The rules determining whether a consensus motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 55 publications
(101 reference statements)
0
27
0
Order By: Relevance
“…We thus investigated the sequence context effect on RNAP pausing between the true and false PIEs. As described below and in our previous studies (24)(25)(26)(27)(28)(29), we have previously revealed that nonconsensus repetitive DNA sequence elements in the vicinity of a consensus protein-binding motif statistically enhance the protein binding to its "site." This finding led us to hypothesize that a similar context effect could provide the mechanism responsible for the genome-wide regulation of RNAP pausing at PIE motifs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We thus investigated the sequence context effect on RNAP pausing between the true and false PIEs. As described below and in our previous studies (24)(25)(26)(27)(28)(29), we have previously revealed that nonconsensus repetitive DNA sequence elements in the vicinity of a consensus protein-binding motif statistically enhance the protein binding to its "site." This finding led us to hypothesize that a similar context effect could provide the mechanism responsible for the genome-wide regulation of RNAP pausing at PIE motifs.…”
Section: Resultsmentioning
confidence: 99%
“…2A (also refs. 26,27). Then, we computed the average free energy difference between the two groups comprising each randomized group pair (i), (ii), and (iii), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-consensus binding of PIC components to the NDR has been suggested to explain binding of general TFs to promoter regions without any discernable recognition sequences [42]. Such binding was promoted by the TF Reb1 in yeast and inhibited by CTCF in human cells [43]. NDRs with two PICs are further characterized by a greater occupancy of the − 1 nucleosome [43], suggesting that the chromatin structure at the NDR promotes opening of a transcription bubble and is conducive to bidirectional transcription, with PICs forming in both directions at the edges of the flanking nucleosomes.…”
Section: Core Promoter Elements Work Synergistically To Establish Tramentioning
confidence: 99%